ULTRASTRUCTURAL CHANGES IN THE MITOTIC APPARATUS AT THE METAPHASE-TO-ANAPHASE TRANSITION - Robbins, Elliott (The Rockefeller University Press, 1969)
As the metaphase HeLa cell approaches anaphase, pericentriolar spindle tubules fragment and become encapsulated by a unit membrane. By early anaphase, the encapsulated forms appear to have expanded, giving rise to polar spherical aggregates. Some of these elements show ribosomes on their bounding membrane, and some of them localize on the condensed chromatin during reformation of the nuclear membrane. It thus is suggested that these elements are newly derived cisternae of the endoplasmic reticulum (ER). Similar transformations are seen in later anaphase in the interzonal region, and it may be that the ER serves as a storage depot for some fraction of depolymerized microtubules. The time and location of the pericentriolar transitions are consistent with their being intimately involved in the mechanics of chromosome separation.